ANALISIS KEMAMPUAN PENGUCAPAN KOSA KATA BAHASA ARAB SISWA KELAS VIII MADRASAH TSANAWIYAH GUPPI RANNALOE GOWA - Kasmawati kasmawati; Mahlani Mahlani (Universitas Muhammadiyah Makassar, 2017)
AbstractArabic Language is one of foreign languages which the spreads has been found in several regions and countries .There is no doubt that Arabic language is absolutely necessary in learning and to go deep into the Knowledge about Islam. This is due to the fact that the books which become the source of Islam religion especially the broader and more complete in general still written in Arabic. The difficulties encountered in learning Arabic are influenced by the lack of knowledge of Arabic in the society. This study aims to find out the ability in pronunciation of Arabic vocabulary at the second grade students in Madrasah Tsanawiyah Guppi Rannaloe Gowa and the obstacles which faced by students in the pronunciation of Arabic vocabulary. This research was conducted at Madrasah Tsanawiyah Guppi Rannaloe Gowa, in particular on second grade class. The method used is qualitative. The methods are used in collecting data by researchers in this study, that is: a) Guidelines for observation, direct observation made with phenomenal systematics are investigated by observing the object of study, b) Interview Guidelines, Relate to data is collected on human attitudes and desires, this technique is well suited for obtaining accurate data. c) oral tests, to see how far Arabic vocabulary is pronounced in answering questions verbally and The results of this study shows that the pronunciation ability in Arabic vocabulary by the second grade students in Madrasah Tsanawiyah Guppi Rannaloe Gowa is still below the average due to the lack of knowledge of Arabic language among the students themselves, this is because most of them come from the Primary school which did not know about Arabic language and do study about that.Keywords: Language, Arabic Language, Vocabulary AbstrakBahasa Arab merupakan salah satu bahasa Asing yang penyebarannya sudah banyak ditemukan di beberapa daerah dan negara.. Sudah tidak diragukan lagi bahwa bahasa Arab mutlak diperlukan dalam mempelajari dan mendalami ilmu pengetahuan Islam. Hal ini disebabkan buku-buku yang menjadi sumber agama Islam terutama yang lebih luas dan lengkap pada umumnya masih ditulis dalam bahasa Arab. Kesulitan yang dihadapi dalam mempelajari bahasa Arab dipengaruhi oleh minimnya pengetahuan bahasa Arab di kalangan masyarakat. Penelitian ini bertujuan untuk mengetahui bagaimana kemampuan pengucapan kosakata bahasa Arab pada sisiwa kelas VIII Madrasah Tsanawiyah Guppi Rannaloe Gowa serta apa saja yang menjadi kendala yang dihadapi siswa dalam pengucapan kosakata bahasa Arab. Penelitian ini dilakukan di Madrasah Tsanawiyah Guppi Rannaloe Gowa,khususnya kelas VIII. Adapun metode yang digunakan bersifat kualitatif. Adapun metode pengumpulan data yang peneliti lakukan dalam penelitian ini, yaitu : a) Pedoman observasi, pengamatan langsung yang dilakukan dengan sistematika fenomenal yang diselediki dengan cara mengamati objek yang diteliti. b) Pedoman wawancara, Berhubungan dengan data yang dikumpulkan menyangkut sikap dan keinginan manusia, maka teknik ini cocok sekali untuk memperoleh data yang akurat. c) tes lisan, untuk melihat seberapa jauh kemampuan pengucapan kosakata bahasa Arab dalam menjawab pertanyaan yang diberikan secara lisan dan. Adapun hasil penelitian ini yaitu Kemampuan pengucapan Bahasa Arab siswa kelas VIII Madrasah Tsanawiyah Guppi Rannaloe Gowa masih di bawah rata-rata dikarenakan minimnya pengetahuan bahasa Arab di kalangan siswa itu sendiri., hal ini disebabkan oleh karena kebanyakan dari mereka berasal dari SD yang belum mengenal bahasa Arab sama sekali dan belum pernah mempelajarinya.Kata kunci : Bahasa, Bahasa Arab, Kosa kata